ANALISIS KINERJA ALAT SUPERHEATER PADA INSTALASI PEMBANGKIT TENAGA UAP - Sugiarto, Tris; Soekardi, Chandrasa (Universitas Pancasakti Tegal, 2012)
This paper presents the performance characteristic of a superheater of boiler power plant evaluated by measuring the working parameters such as pressure, temperature, steam flowrate, and gas temperatures flowing through the equipment as a function of time during 12 months of operation with the aim of providing data on the influence of fouling on superheater performance. These data were used to calculate the change of heat transfer rate with time as fouling deposition progressed. The results showed that after 12 months of operation the heat transfer rate declined by 28% below the initial condition. This condition is probably due to more severe fouling in the equipment. The gas flow rate must be reduced below its design value in order to maintain the design heat duty when the equipment is first placed in service. Thus the equipment will have to be taken out for cleaning at an undesirable time. To avoid these conditions it seems interesting to apply the rational design method providing available information of time dependence of fouling thermal resistance.Keywords : boiler, superheater, maintenance, cleaning interval, fouling, heat load, fouling thermal resistance